Mechanical strain and electric field tunable electronic structure of black/violet phosphorene van der Waals heterostructure: From type I to Z-scheme system. (October 2022) - Lu, Yi-Lin; Dong, Shengjie; Li, Jiesen; Mao, Zhuo; Wu, Yuanqing; Yang, Lu-Lu
Abstract: We reported a new van der Waals (vdW) heterostructure formed by monolayer black phosphorene (BP) and monolayer violet phosphorene, also known as Hittorf's phosphorene (HP). The First-principles calculation showed that the BP/HP heterostructure exhibits a direct band gap (1.43 eV) with distinct type-I band alignment. By applying tensile strains, the BP/HP heterostructure was modified from type-I junction to Z-scheme one, forming the built-in electric field directed from BP to HP which just promotes the separation of photogenerated holes and electrons, whereas compressive strains maintain the type-I band alignment but bring to the bandgap (direct to indirect) and the conductivity (semiconductor to metal) transitions. Moreover, negative electric fields could induce a more steady and robust Z-scheme band alignment over a wide range of the electric field intensities. Our present studies pointed out that this high tunability of the electronic structure in BP/HP vdW heterostructure is suitable for future nanoelectronics and photocatalysts. Graphical abstract: Image 1 Highlights: The black/violet phosphorene heterostructure exhibit type-I band alignment. The built-in electric field at interface promotes the separation of carriers. The Z-scheme band alignment occurs under tensile strains and negative electric fields.